Using digital badges to organize student learning opportunities. Issue 4 (2nd October 2017) - Ippoliti, Cinthya; Baeza, Victor D.
ABSTRACT: A growing trend at universities is to use digital badges (micro-credentialing) for capturing the "soft skills" students gain outside of the classroom. Libraries can use this opportunity to become campus leaders in digital badges, using the system to not only promote their information literacy activities but to coordinate workshop programming offered by various university support services. Two university libraries attempted to accomplish these goals with digital badges. One program focused on offering digital badges to promote library programming, while the other initiated a campus-wide movement with the graduate college to promote workshops offered across university departments for graduate students.